RNA-seq identifies long non-coding RNAs as potential therapeutic targets for human corneal endothelial dysfunction under oxidative stress. (December 2021) - Shan, Kun; Qiu, Jini; Zhou, Rongmei; Gu, Jiayu; Zhang, Xueling; Zhang, Chaoran; Xiang, Jun; Xu, Jianjiang
Abstract: Human corneal endothelial cells (CECs) have limited ability to regenerate in vivo. Oxidative stress has been proposed as one potential reason. Understanding the mechanism of oxidative stress-induced CEC dysfunction might provide novel targets for improving CEC regenerative capacity, and help develop non-surgical therapeutic strategies for CEC dysfunction. Long non-coding RNAs (lncRNAs) are non-coding transcripts with multiple biological functions. The roles of lncRNAs in ocular cells under oxidative stress have been widely studied, such as lens epithelial cells, trabecular meshwork cells, and retinal ganglion cells. In the current study, we established oxidative stress-induced CEC dysfunction model in vitro. By RNA sequencing technology, we identified 824 differentially expressed lncRNAs in CEC dysfunction group, including 667 upregulated lncRNAs and 157 downregulated lncRNAs. We finally demonstrated that CEC functions under oxidative stress, including cellular proliferation, apoptosis, and anti-oxidative stress ability, could be regulated by different lncRNAs, including lncRNA-Z93241.1, lncRNA-XLOC_000818, and lncRNA-AC007952.4. Targeting these lncRNAs might be useful to further elucidate the pathology of CEC dysfunction and develop novel therapeutic strategy. Highlights: LncRNAs are significantly dysregulated in human CECs under oxidative stress. LncRNAs regulate multiple functions of human CECs under oxidative stress. Targeting specific lncRNAs might serve as a novel therapeutic strategy for CEC dysfunction.